#### Answer

$2$

#### Work Step by Step

$\lim\limits_{(x,y) \to (1,1)} \dfrac{(x-y)(x+y)}{x-y}=\lim\limits_{(x,y) \to (1,1)}(x+y)$
Thus, we have $\lim\limits_{(x,y) \to (1,1)} \dfrac{(x-y)(x+y)}{x-y}=1+1=2$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-32187-896-5

ISBN 13:
978-0-32187-896-0

$2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.